PERAN BADAN USAHA MILIKI DESA (BUMDES) SYARI’AH KEMBANG SETANJUNG DALAM PENGUATAN EKONOMI DESA TANJUNG MEDAN, KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Deni Novianti (Jurnal Ilmiah Cano Ekonomos, 2023)
In the context of developing village autonomy, one of the strategies adopted is through the provision of sources of income. This strategy is based on the idea that a village will not be able to exercise autonomy if it does not have adequate funding sources, therefore the existence of BUMDes plays a vital role in strengthening the village economy. The focus of this research is how the role of the Syari'ah Kembang Setanjung Village Owned Enterprise (BUMDes) in strengthening the economy of the village of Tanjung Medan, North Tambusai District, Rokan Hulu Regency. The research approach used is descriptive qualitative approach. There were five research subjects. The research instrument used was observation, interviews and documentation studies. The results of the study show that BUMDes Syari'ah Kembang Setanjung plays a very important role in strengthening the economy of the village of Tanjung Medan, North Tambusai District, Rokan Hulu Regency, namely in encouraging the development of community economic activities, increasing creativity and productive economic opportunities, encouraging the development of micro-enterprises in the informal sector, increasing the village's original income, increasing business opportunities and reducing unemployment to improve the welfare of the poor and as a Center for Community Economic Services.